An introduction to "Records in Contexts": an archival description draft standard. Issue 1 (January 2018) - Pitti, Daniel; Stockting, Bill; Clavaud, Florence
Abstract : Records-in-Contexts (RiC) is a new standard for description which will reconcile and build on the four existing ICA description standards, developing a broader understanding of basic archival principles in which it remains grounded. Thus, for example, the Principle of Provenance can be interpreted in different ways, and does not always fully reflect the social and material complexity of records' origin. Similarly, application of the principle of Original Order may result in the presentation of an order as it existed at only one point only in time. RiC attempts to develop a more expansive understanding of provenance by recognizing that records and the people who create, manage, and use them do not exist in isolation but in complex layers of interrelated, interdependent contexts. Representing this complexity is both helped by, and is informed by, developments in information and communication technologies (including developments within the parallel recordkeeping and cultural heritage communities) which offer the opportunity for separating components, re-combining and inter-relating them, opening domain borders and connecting data between disparate systems. Two aspects of RiC are in development: the Conceptual Model (RiC-CM) which provides a generalized view of archival description, through identification of records-related entities (People-/Record-/Businessrelated), their properties and the relations between them; and the Ontology (RiC-O). RiC-O, which is in an early stage of development, will enable a technical representation of RiC-compliant archival metadata. As a formal Web Ontology Language (OWL), and based on the four principles of usefulness, flexibility, functionality and extensibility, it will enable archival description to become fully visible within a linked open online world.